Cultural Navigation and Multiple Roles: Study of Adaptation of Minangkabau People in Overseas Land in the Perspective of the Proverb "Nan Sakuduang Jadi Saruik, Nan Salapeh Jadi Kambang" - Sari, Avid Leonardo; Yusuf, Ali Anwar (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
This article focuses on immigration in Minangkabau culture and how Minangkabau people assimilate in foreign lands. Using the Minangkabau proverb "Nan sakuduang jadi saruik, nan salapeh jadi kambang" as a theoretical framework, this study examines how the Minangkabau people maintain and preserve their culture while contributing to and assimilating into the new society Identity ("nan sakuduang jadi saruik"). It ('nan salapeh jadi kambang'). Research methods included a literature review, in-depth interviews, and participatory observation of Minangkabau communities in multiple resettlement sites. The results of this study show that despite the challenges and obstacles, the Minangkabau people successfully navigated and adapted to a new culture without losing their own cultural identity. This study provides new insights into immigrant cultural dynamics and adjustment processes in the context of Minangkabau, and has the potential to make a significant contribution to broader cultural and social research.